2021
DOI: 10.1002/solr.202100721
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Field Optical Excitations in Silicon Subwavelength Light Funnel Arrays for Broadband Absorption of the Solar Radiation

Abstract: Broadband absorption is pivotal for the realization of green energy based on solar energy. Decoration of photovoltaic cells with arrays of subwavelength formations provides an efficient means for broadband absorption in thin films. Surface arrays of silicon light funnels (LFs) have been suggested as a promising platform to produce broadband absorption that is considerably superior to other subwavelength arrays such as the well‐known nanopillar (NP) arrays. The current study explores the underlying mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The increased power of the solar cell signifies that more electron‐hole carriers are created and effectively extracted to the conducting layer of the solar cell due to the antireflective effect of the VTES/PF‐127 cover glass. The improvement in the total conversion efficiency of the solar cell validates the light‐trapping ability of the prepared VTES/PF‐127‐based porous structure and can be considered as a promising antireflecting cover glass for a photovoltaic system 47 …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The increased power of the solar cell signifies that more electron‐hole carriers are created and effectively extracted to the conducting layer of the solar cell due to the antireflective effect of the VTES/PF‐127 cover glass. The improvement in the total conversion efficiency of the solar cell validates the light‐trapping ability of the prepared VTES/PF‐127‐based porous structure and can be considered as a promising antireflecting cover glass for a photovoltaic system 47 …”
Section: Resultssupporting
confidence: 54%
“…The improvement in the total conversion efficiency of the solar cell validates the light-trapping ability of the prepared VTES/PF-127-based porous structure and can be considered as a promising antireflecting cover glass for a photovoltaic system. 47 The current work further highlights that the hydrophobic antireflection-coated cover glass not only enhances PV performance but also maintains efficiency due to its good self-cleaning ability. This was tested by subjecting dusty-coated substrate over the solar cell and performing I-V characterization.…”
Section: Solar Cell Performance Evaluationmentioning
confidence: 55%
“…The 4 n 2 limit is based on geometrical optics, and it pursues surface decoration of both sides of the thin film in order to increase the optical power in the film. More recently, it was suggested and demonstrated that the 4 n 2 limit can be exceeded if surface decoration with subwavelength structures is employed. Various light trapping mechanisms were identified to produce broadband absorption enhancement of the sun power with surface subwavelength arrays: low optical impedance using arrays of nanocones and black silicon, forward scattering by surface Mie resonators, increase in local density of states, excitations of Bloch modes, light trapping driven by light concentration and the utilization of nanolenses and light funnels, excitations of localized Mie resonances, ,, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…To make the material absorb optical waves efficiently, people often adopt different incident coupling methods or introduce special structures into the material to affect the distribution of the electric field inside the material and the absorption efficiency of the optical wave to improve the performance of the material. [1][2][3][4][5][6] Since graphene was discovered, 7 2D materials have attracted extensive attention and in-depth research due to their unique structures and excellent performances. However, this attention has mainly focused on the properties of fluorescence emission, [8][9][10] saturation absorption, [11][12][13][14] nonlinear optical response, [15][16][17][18][19][20] and horizontally placed monolayer film form.…”
Section: Introductionmentioning
confidence: 99%